Dry adhesive surfaces based on high density, high aspect ratio, hierarchical polymeric nano-structures - Ho, Audrey Yoke Yee (2012)
Gecko’s dry attachment system has been acknowledged to be the most efficient among all the biological attachment systems. Many attempts have been made to emulate the topographic features of the gecko feet to construct artificial dry adhesive tapes. However, many of the gecko inspired structures produced consisted of linear structures made in soft polymers with relatively low density or low aspect ratio in micron or sub micrometer range. As such, a novel methodology was developed to fabricate hierarchical gecko-inspired dry adhesives consisted of high density, high aspect ratio, hierarchical nano-pillars made on a stiff polymeric material. A method is developed for the controlled fabrication of multi-tiered branched porous anodic alumina (PAA). Subsequently, polymeric gecko inspired dry adhesives were produced using the template by a capillary force mediated nano-imprinting. A numerical model was developed for the prediction of the polymer pillar height to obtain the imprinting parameters for complete polymer filling. This model takes into consideration hitherto neglected surface tension effect, a rather important factor for nano-imprinting. Good agreement was obtained between prediction and experimental results. Rigorous characterization of the synthetic dry adhesives’ shear adhesion performance were conducted in both the macro- and micro- scale regimes for a good understanding of the underlying shear adhesion mechanisms.